Effect of continuous ingestion of a beverage prepared with Lactobacillus gasseri CP2305 inactivated by heat treatment on the regulation of intestinal function. (January 2016) - Sawada, Daisuke; Sugawara, Tomonori; Ishida, Yu; Aihara, Kohtaro; Aoki, Yumeko; Takehara, Isao; Takano, Kazuhiko; Fujiwara, Shigeru
Abstract: Commercialized products containing live lactic acid bacteria (LAB) are available for the purpose of modifying gastrointestinal function. In contrast, the impact of sterilized LAB, especially rod-shaped LAB, on intestinal regulation is not fully understood. Here, we examined the beneficial effects of sterilized Lactobacillus gasseri CP2305 (CP2305) as a "paraprobiotic" on gastrointestinal function in a double-blind, placebo-controlled trial. Subjects (n = 39) were healthy individuals who had a tendency toward constipation (n = 20) or frequent bowel movements (n = 19). They included both genders (15 males and 24 females) and were 20–70 years of age (mean 44.4 ± 12.4 years). Subjects with constipation or frequent bowel movements were randomly divided into two groups, and they ingested either an artificially acidified milk-based placebo beverage or a heat-inactivated CP2305 fermented milk (FM)-based beverage for 3 weeks. Subjects kept a stool diary to record the frequency of bowel movements, the feeling after defecation and the fecal conditions. Fresh fecal samples were collected to evaluate the fecal characteristics and to analyze the fecal metabolites and the composition of intestinal microbiota. The stool characteristics, including the subjective and objective Bristol stool scale scores, output, and color tone, were improved in the heat-inactivated CP2305 FM-based beverage group (CP2305 group), especially in subjects who had a tendency toward constipation. Analyses of the fecal samples showed that the concentrations of short-chain fatty acids (SCFAs) were significantly increased in the CP2305 group. The population of Clostridium cluster IV was significantly increased in the CP2305 group. The heat-inactivated CP2305 FM had a beneficial effect on the regulation of intestinal function. Improvement was observed chiefly in subjects that had a tendency toward constipation. These results suggest that heat-inactivated CP2305 functions as a "paraprobiotic". Highlights: The effect of sterilized Lactobacillus gasseri CP2305 on gut function was confirmed. CP2305 affected the composition of intestinal microbiota. CP2305 significantly improved intestinal microbial metabolism. CP2305 influenced defecation habits.